ANALISIS SISTEM FONOLOGI BAHASA TOLAKI DIALEK KONAWE RAGAM BIASA - Baroroh, Hilma Erfiani (Pujangga : Jurnal Bahasa dan Sastra, 2023)
This study aims to analyze the phonological system of Tolaki language in Konawi dialect of ordinary variety. The research technique was conducted by collecting data through informant interviews from Konawi, Kendari, Southeast Sulawesi. The initial data for the interview material were 200 basic Swadesh vocabularies, which later in the interview process developed into 238 vocabularies. The data was collected using note-taking and recording techniques. The results showed that the Tolaki language in the Konawe dialect has 28 letter sounds consisting of 12 vowel phonemes and 16 consonant phonemes. However, the letters are not phonemic. After going through the minimal pairing process, 9 vowel phonemes were found, namely /a/, /i/, /u/, /e/, /o/, /O/, /a:/, /i: /, and /u:/, and 15 consonant phonemes, namely /b/, /d/, /g/, /h/, /k/, /l/, /m/, /n/, /p/, /r/, /s/, /t/, /w/, /N/, and /Ɂ/. In terms of phonemes, the language lacks allophones and diphthongs (vowel clusters). In addition, the Konawe dialect of Tolaki has relatively more vowel phoneme sequences than consonant phoneme sequences. The syllable patterns formed are V, KV, KVK, KKV, and VK. Keywords: The phonological system, the Tolaki language, the Konawi dialect.